Advance care planning readiness among older adults in aged service centers: A cross-sectional study - Kalok Wong; Haobin Yuan; Stephen Tee; Sinkei Cheong (International Journal of Nursing Sciences)
Objective: This study aimed to explore the readiness for advance care planning (ACP) among older adults in Macau’s day service centers and investigate the influencing factors. Methods: A cross-sectional study was conducted from October to December 2022 using a convenience sampling method. A total of 312 older adults were selected from 13 day service centers for older adults in Macau, China. The Advance Care Planning Acceptance Questionnaire and the Family Adaptation, Partnership, Growth, Affection, Resolve (APGAR) Scale were used to survey the older adults. Results: A total of 306 older adults completed the survey. The score for advance care planning readiness was 65.55 ± 10.69, and 59.5% of participants (n = 182) were willing to participate in ACP. The family function score was 7.24 ± 2.51, while 70.3% of participants were from a highly functional family. The higher family function indicating a higher readiness for advance care planning (r = 0.396, P < 0.001). The multiple linear regression analysis indicated that the variables “age,” “knowledge of ACP,” “experience with ACP,” and “received resuscitation of yourself, relatives or friends” combined with “family function” can influence advance care planning readiness among older adults (R2 = 0.317, F = 27.898, P < 0.001). Conclusions: Older adults in Macau’s day service centers were willing to engage in ACP. The importance of family involvement is highlighted in the ACP readiness. Health education and improved family communication are vital for promoting ACP, which ensures individuals receive care when they lack the capacity to make that choice. Additionally, healthcare professionals should enhance communication and education with older adults during the medical care process.